Matter in extreme conditions produced by lasers. (15th July 2016) - Batani, Dimitri
Abstract: This perspective addresses the study of "extreme" states of matter created by laser pulses. We define "warm dense states" and "high energy density", their importance in physics, how to produce and diagnose them, either using isochoric heating with short-pulse lasers or laser-driven shock waves.